Quality of Choco Chips Cookies with Porang Flour as a Substitute for Wheat Flour - Purwanti, Komang Savitri Dwi; Winata, Gede Adi Sistha; Dalem, Anak Agung K.P.; Hardina, Hardina (PT FORMOSA CENDEKIA GLOBAL, 2024)
Cookies are crispy, thin, flat (flat) cookies, and usually small in size. Cookies have a distinctive aroma and taste because this pastry product uses a lot of butter, one example of cookies that are often consumed is choco chip cookies. The basic ingredient for making these cookies is wheat flour, where wheat flour contains gluten containing lectin, which causes reduced insulin efficiency, slow calorie burning, and decreased metabolic rate in the body. Therefore, some people who suffer from gluten disease are very abstinent from consuming foods made from wheat flour, for example choco chip cookies. Therefore, as another alternative, you can choose porang flour as a substitute for wheat flour. In the health industry, porang plants have benefits, namely that the tuber flour contains glucomannan which is very potential to be developed, because it is easy to obtain and can produce carbohydrates and a high harvest rate, with a neutral taste so that it can be used together with other raw materials in traditional and modern cake processing. Therefore, an experiment was carried out to make choco chip cookies with porang flour as a substitute for wheat flour. By conducting organoleptic tests in this study, namely by giving a questionnaire using a Likert scale to 25 panelists and obtaining results with an index value of 86% which can be interpreted as very good.